Будь ласка, вирішіть q 5?

Будь ласка, вирішіть q 5?
Anonim

Відповідь:

Дивись нижче.

Пояснення:

Ми маємо, #color (білий) (xxx) a ^ (2x - 3) * b ^ (2x) = a ^ (6-x) * b ^ (5x) #

#rArr a ^ (2x - 3) / a ^ (6-x) = b ^ (5x) / b ^ (2x) #

Просто перенесіть # a # і # b # на їхніх відповідних сторонах.

#rArr a ((2x - 3) - (6 - x)) = b ^ (5x - 2x) # Як # a ^ (m-n) = a ^ m / a ^ n #

#rArr a ^ (2x - 3 - 6 + x) = b ^ (3x) #

#rArr a ^ (3x - 9) = b ^ (3x) #

#rArr (a ^ (x - 3)) ^ 3 = (b ^ x) ^ 3 # Як, # (x ^ m) ^ n = x ^ (mn) #

#rArr a ^ (x - 3) = b ^ x #

#rArr a ^ x / a ^ 3 = b ^ x # Як # a ^ (m-n) = a ^ m / a ^ n #

#rArr a ^ x / b ^ x = a ^ 3 # Перенесення знову

#rArr (a / b) ^ x = a ^ 3 # Як # (a / b) ^ m = a ^ m / b ^ m #

#rArr log (a / b) ^ x = log a ^ 3 # Взяття # log # з обох сторін

#rArr x log (a / b) = 3 log a # Як #log a ^ x = x log #

#rArr 3 log a = x log (a / b) #

Звідси доведено.